Rapid Isolation of Mycoviral Double-Stranded Rna from Botrytis Cinerea and Saccharomyces Cerevisiae - Castillo-Nara, A; Sepulveda-Palma, F; Cottet-Bustamante, L (2011)
Background. In most of the infected fungi, the mycoviruses are latent or cryptic, the infected fungus does not show disease symptoms, and it is phenotypically identical to a non-infected strain of the same species. Because of these properties, the initial stage in the search for fungi infected with mycoviruses is the detection of their viral genome, which in most of the described cases corresponds to double-stranded RNA (dsRNA). So to analyze a large number of fungal isolates it is necessary to have a simple and rapid method to detect dsRNA. Results. A rapid method to isolate dsRNA from a virus-infected filamentous fungus, Botrytis cinerea, and from a killer strain of Saccharomyces cerevisiae using commercial minicolumns packed with CF11 cellulose was developed. In addition to being a rapid method, it allows to use small quantities of yeasts or mycelium as starting material, being obtained sufficient dsRNA quantity that can later be analyzed by agarose gel electrophoresis, treated with enzymes for its partial characterization, amplified by RT-PCR and cloned in appropriate vectors for further sequencing. Conclusions. The method yields high quality dsRNA, free from DNA and ssRNA. The use of nucleases to degrade the DNA or the ssRNA is not required, and it can be used to isolate dsRNA from any type of fungi or any biological sample that contains dsRNA. © 2011 Castillo et al; licensee BioMed Central Ltd.